3D printed removable functional appliances for early orthodontic treatment: possibilities and limitations - Segnini, Cristiano; D'Antò, Vincenzo; Antonio, Nappo; Roser, Christoph; Knode, Vanessa; Björn, Ludwig (Seminars in orthodontics, 2023)
The early treatment of certain malocclusions, such as class II division 1, is recommended to decrease the likelihood of upper incisor trauma. However, the lack of skilled technicians and economic constraints prevent the availability of well-known removable functional appliances. The orthodontic profession is undergoing changes, and automation may offer a solution to these challenges. This article discusses the potential for automating the production of two commonly used removable orthodontic appliances. While CAD-CAM systems have streamlined dental manufacturing, 3D printing is a popular option for certain manufacturing processes. However, the adoption of 3D printing for orthodontic devices faces hurdles, such as redesigning devices for this new manufacturing process, material considerations, and necessary certifications. To showcase the potential design and manufacturing process of 3D printed devices that fall under the category of appliances similar in type and style to FR II and Sander II, the article centers on these two widely recognized appliances. As it is currently not possible to replicate all analog features in 3D, it may be appropriate to use a more general name for the FR II and Sander II appliances. In summary, the article examines the potential and limitations of automation in orthodontic appliance manufacturing.